Analisis Pengaruh Kepuasan Kerja dan Pengembangan Karier terhadap Kinerja Karyawan PT. TRM - Aidil Putra; Yusuf Taufik (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
This study investigates the influence of job satisfaction and career development on employee performance at PT. TRM. The research adopts a quantitative explanatory approach to explain causal relationships among variables. Data were obtained from the entire population of 32 employees using a structured questionnaire measured with a Likert scale and were complemented by relevant company documentation. Prior to hypothesis testing, the data were examined using classical assumption tests to ensure the suitability of the regression model. The analytical method employed was multiple linear regression. The results demonstrate that job satisfaction and career development simultaneously exert a positive and statistically significant effect on employee performance. When analyzed individually, each variable also shows a positive and significant influence. However, career development contributes more dominantly to performance improvement compared to job satisfaction. This finding indicates that opportunities for career growth, including clear career paths, training programs, and transparent promotion systems, play a crucial role in enhancing employee productivity and effectiveness. The study implies that PT. TRM should prioritize the strengthening of career management practices as a strategic effort to improve performance outcomes. At the same time, the company needs to consistently maintain key aspects of job satisfaction, such as fair compensation, supportive leadership, and a comfortable working environment, to sustain employee motivation and commitment.